A novel reconfigurable FSS applied to the antenna radar cross section reduction. Issue 7 (21st March 2019) - Wang, Fuwei; Li, Ke; Ren, Yuhui; Zhang, Yunqi
Abstract: Active reconfigurable FSS using pin diode for the antenna radar cross section (RCS) reduction is proposed. The reconfigurable FSS reflector is presented in this article. The proposed reconfigurable FSS reflector is able to be switched between band‐stop FSS with OFF‐state diodes and band‐pass FSS with ON‐state diodes around 3.8 GHz. The using of band‐stop FSS reflector corresponds to the out‐band RCS reduction during radar operating, and the using of band‐pass FSS reflector corresponds to the in‐band RCS reduction during radar nonoperating. Therefore, the state of the antenna scattering can be switched according to the working state of radar. The results show that the reconfigurable FSS reflector can contribute to the switchable RCS reduction between in band and out band of the antenna. The radiation performance of the antenna is preserved when the diodes are ON state. The monostatic RCS of the antenna with FSS reflector with ON‐state diodes can be reduced more than 25 dB at operating band, and the out‐band RCS reduction can be achieved with ON‐state diodes.